Specific and Rapid Glucose Detection Using NAD‐dependent Glucose Dehydrogenase, Diaphorase, and Osmium Complex. Issue 5 (6th February 2019) - Haque, Al‐Monsur Jiaul; Nandhakumar, Ponnusamy; Yang, Haesik
Abstract: Selective glucose measurement in serum and blood and rapid glucose measurement using nicotinamide adenine dinucleotide (NAD)‐dependent glucose dehydrogenase (NAD‐GDH) are still very challenging. Here, we report a selective and rapid glucose sensor, based on electrochemical‐enzymatic‐enzymatic (ENN) redox cycling involving bis(2, 2‐bipyridyl)dichloroosmium(II) [Os(bpy)2 Cl2 ], diaphorase (DI), NAD +, NAD‐GDH, and glucose. DI and Os(bpy)2 Cl2 are used to obtain fast mediated oxidation of NADH that is generated as a result of glucose oxidation by NAD‐GDH. DI and NAD‐GDH are co‐immobilized via affinity binding on an avidin‐modified indium tin oxide electrode to obtain fast and stable ENN redox cycling. Two enzymes (DI and NAD‐GDH) and two electron mediators [Os(bpy)2 Cl2 and NAD + ] are insensitive to oxygen. The applied potential (0.0 V vs Ag/AgCl) is low enough to minimize interfering electrochemical reactions, and the redox reactions of Os(bpy)2 Cl2 with interfering species are slow. NAD‐GDH is much less reactive to problematic monosaccharides such as xylose, fructose, galactose, and mannose than glucose. Artificial serum containing 5 % (w/v) human serum albumin shows a similar electrochemical background level in serum. All results enable us to obtain selective and reproducible glucose detection. The fast ENN redox cycling allows sensitive glucose detection with a wide range of concentrations in artificial serum with a short measuring time (5 s) without an incubation period. Abstract :